PENGARUH BAHASA HOKKIEN DALAM DIALEK BETAWI DAN PENGGUNAANNYA SEBAGAI BAHASA GAUL DI KOMENTAR MEDIA APLIKASI TIKTOK - Syaharani, Azzahra; Saddhono, Kundharu (Universitas Islam Malang, 2024)
This article discusses the influence of Hokkien in the Betawi dialect and its use as slang in media comments on the TikTok application. This research aims to understand the role of the Hokkien language in forming the Betawi dialect and how its use has become a characteristic feature in TikTok comments. The research method used is content analysis of comments using Hokkien on TikTok. Research findings show that the use of Hokkien in the Betawi dialect on social media, especially TikTok, has an important role in strengthening cultural identity and enriching language expression in daily communication. This article provides new insight into the influence of Hokkien in the Betawi dialect and its use as slang in the TikTok application media.